Acumulacion de carbono en la biomasa de Leucaena leucocephala y Guazuma ulmifolia asociadas y en monocultivo - Casanova Lugo, F.=700 1 Caamal Maldonado, J.; Petit Aldana, J.; Solorio Sanchez, F.; Castillo Caamal, J.
(Es, En)
Ilus., 21 ref
Keywords: LEUCAENA LEUCOCEPHALA; GUAZUMA ULMIFOLIA; PLANTAS LEÑOSAS; CARBONO; BIOMASA; FOLLAJE; HOJARASCA; VENEZUELA; REVISTA FORESTAL VENEZOLANA